Granulocyte concentrates prepared from residual leukocyte units produced by the Reveos automated blood processing system. (April 2020) - Sahlin, Angelica; Blomgran, Robert; Berlin, Gösta
Abstract: Background: Granulocyte concentrates are mainly derived by apheresis technique from donors stimulated with granulocyte colony-stimulating factor and steroids. The automated blood processing system Reveos, which is now increasingly used across the world, separates whole blood into four components, including a residual leukocyte unit containing granulocytes. The aim of this study was to produce an alternative granulocyte concentrate from leukocyte units produced by the Reveos system, and to assess the function of the granulocytes. Methods: The number of granulocytes was measured in residual leukocyte units, derived from whole blood donations, with different volumes ranging from 10 to 40 ml. After deciding the optimal volume of the leukocyte unit (30 ml), ten ABO-matched units were pooled to form a granulocyte concentrate. The function of the granulocytes from residual leukocyte units was assessed by analyzing surface markers, phagocytosis of yeast, and production of reactive oxygen species. Results: Residual leukocyte units with a volume of 30 ml contained a median number of 0, 7 × 10 9 granulocytes, and granulocyte concentrates prepared from ten pooled 30 ml-leukocyte units contained a median number of 6, 3 × 10 9 granulocytes. Granulocytes derived from residual leukocyte units displayed surface markers associated with granulocyte function, and capability to phagocytose yeast and produce reactive oxygen species. Conclusions: Granulocyte concentrates prepared from residual leukocyte units contain in vitro functional granulocytes and may be considered as an alternative product in acute situations before regular granulocyte concentrates from stimulated donors are available.